Ceramic foams coated with PtNi/CeO2ZrO2 for bioethanol steam reforming. (20th July 2016) - Palma, V.; Ruocco, C.; Ricca, A.
Abstract: The catalytic activity of bimetallic PtNi/CeO2 ZrO2 powders and foams, with a silicon carbide carrier and containing silica or boehmite as binder, was investigated for ethanol steam reforming in the low temperature range (400–500 °C). A parametric experimental study was preliminary performed to analyze the effect of different operative conditions (temperature, water/ethanol ratio and contact time) on coke selectivity: low temperatures and space velocities as well as high water contents in the feeding stream minimized carbon deposits formation and reactor plugging. Moreover, once analyzed the individual influence of C2 H4 O, C3 H7 OH, C4 H9 OH and C5 H11 OH, selected among the main bioethanol contaminants, on catalyst deactivation, a model mixture, containing 1% mol of all the impurities, was fed to the reformer at 15, 000 h −1, T = 450 °C and water/ethanol ratio equal to 6. In order to test catalytic behavior in more stressful conditions, contact time was decreased and the stability of powder and foam catalysts was investigated at 50, 000 h −1 . Despite very similar H2 selectivities were recorded, the structured samples, containing boehmite as binder, showed the most interesting catalytic performance, as total ethanol conversion was assured for more than 1 day of time-on-stream. Foams geometry, in fact, enhanced coke gasification reactions, limiting, at the same time, plugging phenomena. Highlights: PtNi/CeO2 ZrO2 powder and foam catalysts showed excellent performances in ESR. Low temperatures, space velocities and high fed water minimized carbon deposition. Heavier molecule impurities increased coke formation without effect on conversion. Boehmite-based catalysts showed higher resistance to deactivation than silica-based.